2013
DOI: 10.1016/j.jeurceramsoc.2012.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Production of nepheline/quartz ceramics from geopolymer mortars

Abstract: This research has investigated the mechanical properties and microstructure of metakaolin derived geopolymer mortars containing 50% by weight of silica sand, after exposure to temperatures up to 1200 °C. The compressive strength, porosity and microstructure of the geopolymer mortar samples were not significantly affected by temperatures up to 800 °C.Nepheline (NaAlSiO 4 ) and carnegieite (NaAlSiO 4 ) form at 900 ºC in the geopolymer phase and after exposure to 1000 °C the mortar samples were transformed into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 32 publications
8
74
1
Order By: Relevance
“…Crystallization of nephaline (NaAlSiO 4 ) from kaolin geopolymer gradually occurred on heating. Kuenzel et al [13], and Markovic et al [14], found similar finding that nephaline detected after the geopolymer exposed to high temperature. The phase analysis for each sample with incorporation amount of 2, 4, 6 and 8 wt.…”
Section: Resultssupporting
confidence: 52%
“…Crystallization of nephaline (NaAlSiO 4 ) from kaolin geopolymer gradually occurred on heating. Kuenzel et al [13], and Markovic et al [14], found similar finding that nephaline detected after the geopolymer exposed to high temperature. The phase analysis for each sample with incorporation amount of 2, 4, 6 and 8 wt.…”
Section: Resultssupporting
confidence: 52%
“…The major activation products present in both binders are amorphous, with a certain amount of unreacted mullite and quartz. When exposed to 800°C for 3 h, some of the amorphous phases in F5S0 crystallize into nepheline (NaAlSiO4), which is often found in heated geopolymers [34,46,47]. In F5S30, the diffraction peaks attributed to nepheline are much more intense than in F5S0.…”
Section: Thermal Resistancementioning
confidence: 99%
“…Most frequently granular fillers are used for this purpose, such as silica sand [24], calcite and dolomite sand [25], grinded electrical porcelain [26], grinded high-alumina refractory brick [27], aAl 2 O 3 powder [28], a-quartz sand and fine alumina powder [29], chamotte powder [30], kyanite (nesosilicate) aggregates [31], cordierite powder [32], burned clay [33], expanded clay [34], quartz fume [35]. Besides, fiber reinforcement was applied such as SiC fibers [36], basalt fibers [37], also steel or polymer fibers [38].…”
Section: Introductionmentioning
confidence: 99%